Bridging brand parity with insights regarding consumer behavior - Ömer Turunç; Cem Karayalçin (Economics: The Open-Access, Open-Assessment Journal, 2024)
Previous research has investigated some of the relationships among brand parity (BP), brand image (BI), brand satisfaction (BS), and brand loyalty (BL). However, there is not a model investigating all of them in a single conceptual model. Based on information processing theory, the first aim of the article is to investigate the important, direct effect relationships among these variables. Moreover, scant information is available regarding the moderating role of BP. Consequently, the second purpose of the study is to test the moderating effect of BP regarding the effect of BI on BL and BS on BL. The data were collected from customers of chain stores in Antalya. The results supported the positive, direct effect of BI on BS and BL, plus BS on BL. There were no direct and moderating effects of BP. Based on the microeconomic behavior of consumers and because of the bounded rationality of consumers, as BP rises, consumers' decisions are not affected regarding the effect of BI on BL and BS on BL. This is an important insight that brands should consider in terms of points of parity associations that affect consumers' decision-making process and create a brand-loyal customer base.
Keywords: D29; M30; M31; 330; brand parity; brand image; brand preference; brand loyalty; microeconomics; consumer behavior